2023
DOI: 10.1073/pnas.2216458120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of chemokine-like receptor 1 (CMKLR1) in experimental acute lung injury

Abstract: The lack of techniques for noninvasive imaging of inflammation has challenged precision medicine management of acute respiratory distress syndrome (ARDS). Here, we determined the potential of positron emission tomography (PET) of chemokine-like receptor-1 (CMKLR1) to monitor lung inflammation in a murine model of lipopolysaccharide-induced injury. Lung uptake of a CMKLR1-targeting radiotracer, [ 64 Cu]NODAGA-CG34, was significantly increased in lipopolysaccharide-induced injury, correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 69 publications
5
23
0
Order By: Relevance
“…The significance of Cmklr1 (chemokine-like receptor-1) is not fully understood [ 127 , 128 ]. Cmklr1 deficiency reduces leukocyte recruitment to inflammation-damaged lungs [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of Cmklr1 (chemokine-like receptor-1) is not fully understood [ 127 , 128 ]. Cmklr1 deficiency reduces leukocyte recruitment to inflammation-damaged lungs [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, activation of Cmklr1 in a murine model of virus-induced pneumonia improved viral clearance and antiviral antibody production, reduced the expression of pro-inflammatory mediators, reduced complications, and improved mouse survival [ 129 , 130 ]. While clinical data are still lacking, preclinical data suggest that Cmklr1 may be a lung inflammation biomarker in pneumonia patients [ 128 ]. The enzyme NOS2 (nitric oxide synthase 2) and reactive oxygen species (ROS) are players in inflammatory and immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical relevance of CMKLR1 as a marker of lung inflammation in ARDS was confirmed using RNA sequencing data, which showed that CMKLR1 expression is significantly increased in lung monocytes and macrophages in COVID-19 patients. CMKLR1-targeted PET is essential for monitoring the dynamics of lung inflammation and response to anti-inflammatory therapy [ 125 ]. The pro-inflammatory chemokine receptors CCR1, CCR2, CXCR3, and CX3CR1 mediate the immune response in the lung and are present in myeloid cells, T cells, and NK cells [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the PET tracer [ 64 Cu]DOTA-ECL1i is reported to target CCR2-expressing monocytes [ 60 , 61 ], which have been demonstrated to be relevant in pulmonary inflammation and noninvasively monitors response to immunotherapies. Additionally, we have recently reported that [ 64 Cu]NODAGA-CG34, a PET tracer that selectively binds to chemokine-like receptor-1 (CMKLR1), detects the accumulation of monocyte-derived macrophages in the lungs of mice with ALI [ 62 ]. Other emerging molecular imaging targets include, α 4 β 1 integrin [ 63 ], leukocyte receptor CD11b [ 64 ], folate receptor-β [ 65 ], and translocator protein receptor [ 66 ], which have been successfully used for noninvasive detection of lung inflammation in ALI.…”
Section: Discussionmentioning
confidence: 99%